Manipulation of tribological properties of stainless steel by picosecond laser texturing and quenching. (July 2016) - Wang, Zhuo; Wang, Cheng-Wei; Wang, Min; Zhao, Quan-Zhong
Abstract: We reported on the manipulation of tribological properties of stainless steel by picosecond laser texturing and quenching. The micro-grooved textures were formed on the steel surface, accompanied with the appearance of nanostructures with grain sized of 80–400 nm, oxides thin film (Fe2 O3 and Cr2 O3 ) and martensite during picosecond laser surface texturing process. The tribological tests indicated that the average friction coefficients and wear rates of textured surfaces initially increased then decreased with the increase of spacing of micro-grooves. The well-controlled friction and wear properties are attributed to the combined effects of induced micro-/nanostructures, martensitic transformation and oxides thin film in the local quenched zone of stainless steel samples. Highlights: Micro-/nanostructures are produced by picosecond laser. Surface textures and local quenching are simultaneously induced by picosecond laser. Tribological properties of stainless steels can be tuned by picosecond laser treatment.